2021
DOI: 10.3390/ijerph18020829
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study to Develop and Test Palliative Care Quality Indicators for Nursing Homes

Abstract: An increasingly frail population in nursing homes accentuates the need for high quality care at the end of life and better access to palliative care in this context. Implementation of palliative care and its outcomes can be monitored by using quality indicators. Therefore, we developed a quality indicator set for palliative care in nursing homes and a tailored measurement procedure while using a mixed-methods design. We developed the instrument in three phases: (1) literature search, (2) interviews with expert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The indicators and methods such as health facility surveys are highly transferable and could be used to measure quality of care in other countries. Similarly, Dupont et al, (2021) (22) reported that using both quantitative and qualitative analyses and instruments had good face validity, feasibility, discriminative power, and it is useful in terms of quality monitoring by caregivers. On the same line, Báo, Amestoy, Moura& Trindade, (2019) (23) stated that quality indicators are a tool for improving care, assisting nurses in knowing the patients whom care is provided to, helping the clinical decision-making regarding best practices in health care, assisting nurses in the work process through stimulating the critical thinking and favoring a better understanding of care, as well as promoting the prevention of future damages and mistakes in this practice.…”
Section: Discussionmentioning
confidence: 99%
“…The indicators and methods such as health facility surveys are highly transferable and could be used to measure quality of care in other countries. Similarly, Dupont et al, (2021) (22) reported that using both quantitative and qualitative analyses and instruments had good face validity, feasibility, discriminative power, and it is useful in terms of quality monitoring by caregivers. On the same line, Báo, Amestoy, Moura& Trindade, (2019) (23) stated that quality indicators are a tool for improving care, assisting nurses in knowing the patients whom care is provided to, helping the clinical decision-making regarding best practices in health care, assisting nurses in the work process through stimulating the critical thinking and favoring a better understanding of care, as well as promoting the prevention of future damages and mistakes in this practice.…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue also comprises intervention studies, with interventions aimed at addressing depressive symptoms in nursing home residents [10,11], adjustment for new residents [12], social and psychological support [13], and loneliness and isolation [14]. Other studies present evidence which developed and tested quality indicators [15,16], and tools which capture the experience of quality from a resident's perspective [17,18], and assess partnership working between staff and families [19]. We also included studies that investigated factors associated with older people's experiences, such as the association between length of stay and end of life care [20], dry eyes or ocular lubricants with medication use, dementia, frailty and dry eyes [21], resident characteristics and their palliative care service use and comfort in the last week of life [22] and causes of infection-related hospitalizations [23].…”
mentioning
confidence: 99%